Indonesian Traditional Ulama Notions Against Wahhabism: A Study of Abi al-Faḍal al-Senoriy’s Thought - Muhammad Asif (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
Studies of the early 19th century on the classical literatures of traditional Indonesian Muslim scholars in response to Wahhabi developments have forgotten the important work of Kawākib al-Lammā‘ah written by Abi al-Faḍal al-Senoriy. This book emerged in the midst of a situation of massive expansion of Wahhabi teachings and of intense debate among modernist and traditional Muslim groups in Indonesia. This book also represents Nahdlatul Ulama’s response towards Wahhabi teachings because the 23rd Nahdlatul Ulama Conference in Solo in 1964 was recommended to be a referred book in pesantrens and other educational institutions of the Nahdlatul Ulama. Through descriptive-qualitative analysis, this article examines the thought of Abi al-Faḍal al-Senoriy in the particular book. This article finds that Abi al-Faḍal has carried out a critical study on Wahhabi teachings, which according to him opposes Sunni teachings for the Wahhabi teachings contradict some important foundation in the Ahl al-Sunnah Islamic tradition in terms of theology, fiqh, and Sufism.